The Associations of Childhood Psychosocial Factors With Cognitive Function in Midlife-The Young Finns Study - Nurmi Amanda; Pulkki-Råback Laura; Salo Pia; Pahkala Katja; Juonala Markus; Hutri-Kähönen Nina; Kähönen Mika; Lehtimäki Terho; Jokinen Eero; Keltikangas-Järvinen Liisa; Laitinen Tomi P.; Tossavainen Päivi; et al. (AMER PSYCHOLOGICAL ASSOC, 2025)
Objective: An adverse psychosocial environment in childhood may harm cognitive development, but the associations for adulthood cognitive function remain obscure. We tested the hypothesis that adverse childhood psychosocial factors associate with poor cognitive function in midlife by leveraging the prospective data from the Young Finns Study.
Method: At the age of 3–18 years, the participants’ psychosocial factors (socioeconomic and emotional environment, parental health behaviors, stressful events, child’s self-regulatory behavior, and social adjustment) were collected. In addition to the separate
psychosocial factors, a score indicating their clustering was created. Cognitive function was measured at the age of 34–49 years with a computerized test addressing learning and memory (N = 1,011), working memory (N = 1,091), sustained attention and information processing (N = 1,071), and reaction and movement time (N = 999).
Results: We observed an inverse association between the accumulation of unfavorable childhood psychosocial factors and poorer learning and memory in midlife (age, sex, education, adulthood smoking, alcohol drinking, and physical activity adjusted β = −0.032, SE = 0.01, p = .009). This association corresponded approximately to the effect of 7 months aging. Specifically, poor self-regulatory behavior (β = −0.074, SE = 0.03, p = .032) and social adjustment in childhood (β = −0.111, SE = 0.03, p = .001) associated with poorer learning ability and memory 30 years later. No associations were found for other
cognitive domains.
Conclusions: The findings suggest an association of childhood psychosocial factors
with midlife learning ability and memory. If these links are causal, the results highlight the importance of a child’s self-regulation and social adjustment as plausible determinants for adulthood cognitive health.